2018
DOI: 10.1177/1753466618800618
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib in the management of idiopathic pulmonary fibrosis: clinical trial evidence and real-world experience

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fibrotic interstitial lung disease associated with significant morbidity and mortality. Previously, IPF has been managed using immunosuppressive therapy; however, it has been shown that this is associated with increased mortality. In the last 5 years, two disease-modifying agents have been licensed for use in IPF, namely pirfenidone and nintedanib. Nintedanib is a tyrosine kinase inhibitor with antifibrotic properties that has also been shown to significantly reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 51 publications
(53 reference statements)
1
54
0
3
Order By: Relevance
“…Furthermore, Ning et al [2] reported that down-regulation of miRNA-326 was strongly associated with intrauterine adhesion, characterized by endometrial fibrosis and high levels of TGF-β1, α-SMA, COL1A1, and fibronectin, as we observed in the present study. Recently, two small molecules (pirfenidone and nintedanib) were approved for idiopathic pulmonary disease, as they showed combinatorial anti-inflammatory, antioxidant, and antifibrotic effects [24,25]. Moreover, Kim et al [18] reported that eupatilin treatment attenuated the progression of bleomycin-induced lung fibrosis and TGF-β-induced fibrotic activity in hepatic stellate cells by disturbing Smad3 phosphorylation, which subsequently led to myofibroblast dedifferentiation and reversal of fibrotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ning et al [2] reported that down-regulation of miRNA-326 was strongly associated with intrauterine adhesion, characterized by endometrial fibrosis and high levels of TGF-β1, α-SMA, COL1A1, and fibronectin, as we observed in the present study. Recently, two small molecules (pirfenidone and nintedanib) were approved for idiopathic pulmonary disease, as they showed combinatorial anti-inflammatory, antioxidant, and antifibrotic effects [24,25]. Moreover, Kim et al [18] reported that eupatilin treatment attenuated the progression of bleomycin-induced lung fibrosis and TGF-β-induced fibrotic activity in hepatic stellate cells by disturbing Smad3 phosphorylation, which subsequently led to myofibroblast dedifferentiation and reversal of fibrotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Nintedanib (BIBF1120), an inhibitor of PDGFR, vascular endothelial growth factor receptor (VEGFR), and fibroblast growth factor receptor 1 (FGFR1), was initially studied for its role in angiogenesis inhibition, but its importance in the treatment of fibrotic disease derives from the ability to suppress myofibroblast differentiation and to reduce collagen deposition [111]. Recent clinical trials have shown the efficacy and tolerability of Nintedanib in lung fibrosis treatment [112,113]. Moreover, it has been shown that in combination with traditional chemotherapy, BIBF1120 improves clinical outcomes in terms of response rate and progression-free survival in non-small cell lung cancer patients [114,115].…”
Section: Translational Potential Of Anti-fibrotic Agents For Melanomamentioning
confidence: 99%
“…Two pharmacological therapies (nintedanib and pirfenidone) have been shown to slow decline in lung function in patients with IPF [1][2][3][4][5]. The United States Food and Drug Administration and European Medicines Agency approvals of nintedanib and pirfenidone changed the treatment paradigm in IPF and increased understanding of the underlying disease mechanisms [5]. However, these approvals raised new questions in the management of ILD, and prior unmet needs remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%